Ketenimine multicomponent strategy for multifaceted amidine functionalization of peptides on the solid phase - Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Angewandte Chemie-International Edition, 2025)
The amidine group and its derivatives serve as proteolytically stable bioisosteres of the peptide bond, and their selective incorporation into peptides attributes significant chemical and biological features. This study introduces an efficient synthesis of amidine-containing peptides by a copper-catalyzed, solid-phase-compatible multicomponent reaction (MCR), leveraging ketenimine intermediates that are generated in situ. Through the reaction of sulfonyl azides with terminal alkynes and a wide variety of amines, we establish the robust on-resin synthesis of delta/epsilon-amidine amino acids, arginine isologues, fluorescently labeled peptides, drug-peptide hybrids, and PEGylated derivatives. This strategy notably supports a wide range of peptide modifications, including side chain alteration, amine functionalization, and peptide macrocyclization through both backbone and side chain groups, as well as incorporating aromatic scaffolds into the peptide backbone. The methodology demonstrates broad substrate tolerance, compatibility with peptide chemistry protocols, and access to complex motifs, including pharmacophores and imaging tags, all within a single reaction platform. Our results underscore the synthetic versatility and functional applicability of ketenimine-based MCRs for advanced peptide modification, expanding the chemical space of peptide medicinal chemistry and therapeutics.
Keywords: Amidines; multicomponent reactions; peptide modification; Peptide-small molecule hybrids; Solid phase peptide synthesis

Peptide functionalization with dithioate and trithioate groups: A CS2-mediated solid-phase approach - Shinde, Dinesh R.; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Organic Letters, 2025)
The dithiocarbamate group is an important class of compounds whose presence in small molecules and peptides leads to antimicrobial, anticancer, and enzyme inhibition properties. This study introduces an efficient and selective method for incorporating dithioate and trithioate moieties into amino acids and peptides using CS2 chemistry under mild conditions. Utilizing a N,N-diisopropylethylamine (DIPEA)-CS2-benzyl chloride system, we achieved modifications at the N-terminal amines and the side chains of Lys and Cys residues through solid-phase peptide synthesis (spps). The method exhibits excellent yields and broad compatibility with diverse amino acids, their protection groups, peptide chemistry reagents, and varied peptide sequences. Notably, the successful incorporation of trithioate groups into peptides via cysteines, reported here for the first time, expands the functional repertoire of peptide chemistry, offering new possibilities for peptide-based drug design and related applications.

Peptide-triazolobenzodiazepine hybrids: a catalyst-free on-resin strategy to build complex therapeutic motifs into peptides - Kamble, Sandip Sushila Mohan; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Chemistry-A European Journal, 2025)
The merger of peptide and heterocyclic chemistry presents significant opportunities for enhancing the structural and functional diversity of therapeutic agents. In this study, we introduce a streamlined on-resin method to modify peptides at the N-terminus amines and the side chain amines of Lys/Orn amino acids by incorporating the biologically active triazolobenzodiazepine scaffold. In the presented solid-phase peptide synthesis (SPPS), the triazolobenzodiazepine core is formed on-resin through a combination of N-alkylation, amide bond formation, and an alkyne-azide 1,3-dipolar cycloaddition, of which the latter two happen as a single-step one-pot reaction- proceeding under mild conditions without metal catalysts. This protocol tolerates a wide variety of amino acids and functional groups, providing a versatile method for synthesizing peptide-triazolobenzodiazepine hybrids. Using orthogonal protection group strategies, we further demonstrate the method's adaptability for two site modifications in peptides involving both the N-terminus and Lys side chain amines. These modifications enhance the scope of ``peptide medicinal chemistry'' by creating multifunctional peptides with potential therapeutic applications. The method's compatibility with SPPS, room temperature conditions, and elimination of metal catalysis make it an efficient and powerful tool for peptide modification.
Keywords: hybrid peptides; peptide chemistry; peptide modification; spps compatibility; triazolobenzodiazepines